Clinical management of common presentations of patients diagnosed with BPD during the COVID-19 pandemic: the contribution of the MBT framework. Issue 3 (2nd October 2021) - Ventura Wurman, Tamara; Lee, Tennyson; Bateman, Anthony; Fonagy, Peter; Nolte, Tobias
ABSTRACT: The coronavirus (COVID-19) pandemic has both a profound effect on mental health and affects how psychosocial interventions are delivered. In this paper, we outline particular difficulties patients with Borderline Personality Disorder (BPD) may encounter as a result of the pandemic. We also consider changes in the provision of treatment, specifically the transition from face to face encounters to remotely delivered sessions. Building on a mentalization-based developmental framework, we use clinical vignettes to chart some of these challenges for patients, clinicians and teams. We then make practical recommendations for adaptations to work during the pandemic via the phone or video-link with BPD patients and other groups characterized by a vulnerability to unstable and imbalanced mentalizing. We conclude that the response to these challenges benefits from an existing treatment context that aims at fostering mentalizing and resilience, in which practitioners address the hierarchy of patient needs and their individual responses to the experience of remote treatment during the COVID-19 pandemic.